High-Performing and Low-Performing Schools in Makassar Indonesia - Hasmirati Hasmirati; Ishak Sin; Abdul Latif Kassim (Journal of Research and Multidisciplinary, 2020)
Although the Education Department of South Sulawesi Province reported that the performance of Secondary Schools in Makassar is at unsatisfactory level, but there were some schools achieved high performance level. The varying performance of the schools has prompted the researcher to conduct a multi-site case study to identify whether leadership styles of principals have any relationship with high-performing and low-performing schools in Makassar. In order to achieve the objective of this study, a qualitative approach, using multi-case study research design was utilized. Semi-structured interviews, observations, and document analysis were used to collect data. The sample consisted of two high performing and two low-performing secondary schools in the city of Makassar. Four school principals and 12 teachers of the schools were purposely chosen as respondents of the study. Data were analysed using theme analysis technique. This study found that principals in high-performing schools and low-performing schools were used the different styles of leadership. High-performing schools’ principals emphasized more on teaching and learning, controlling students’ discipline, ensuring teachers’ understanding of the school’s vision, and conducting staff developmental programs. This study has contributed to the development of knowledge in the field of high-performing schools in Indonesia. This study suggests that if a school wants to achieve high-performing level, principals must ensure that the teachers teach and students learn.